Experiencias investigativas en el marco del iii congreso internacional de educación a distancia y virtual - Herrera Becerra, María Olga (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This academic event aimed to open an interdisciplinary discussion space that allowed sharing experiences of experts from other countries in the management of biodiversity and at the same time provide a contribution with the purpose of ge- nerating environmental conservation policies as well as guidelines. The Congress is structured from three aspects; organizational; development and impact; in the organizational aspect, different educational, technological, health and pedagogical levels were taken into account; in the development the participation of teachers, experts in training and professional researchers at local, regional, national and international level was evidenced. Finally, the impact caused was the contribution of tools that allow a responsible and solidary management of resources.